Religious coping and psychological well-being among Iranian stroke caregivers - Gholamzadeh, Sakineh; Tengku Abdul Hamid, Tengku Aizan; Basri, Hamidon; Sharif, Farkhondeh; Ibrahim, Rahimah (Isfahan University of Medical Sciences, 2014)
Background: This study aims to explore the relationship between religiosity and psychological well-being of caregivers of stroke survivors in Shiraz, Iran. Materials and Methods: A purposive sample of 96 family members, which included 34 daughters-in-law and 62 daughters, who were caring for severe impaired stroke survivors were enrolled in the study. Results: The results showed a significant correlation between positive religious coping and caregivers’ psychological well-being. Positive religious coping accounted for 7.2% of the change in psychological well-being. There was no significant association between demographic factors and caregivers’ psychological well-being. Conclusions: Our results indicated that religious and spiritual belief have a role in caregiver adaptations with the situation. Therefore, in future studies, it is suggested to concentrate on the effects of other characteristics than the demographic variables on psychological well-being.